2016
DOI: 10.1002/hyp.10870
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of soil pore water extraction methods for stable isotope analysis

Abstract: Measurements of δ 2 H and δ 18 O composition of pore waters in saturated and unsaturated soil samples are routinely performed in hydrological studies. A variety of in-situ and lab-based pore water extraction methods for the analysis of the stable isotopes of water now exist.While some have been used for decades (e.g. cryogenic vacuum extraction) others are relatively new, such as direct vapor equilibration or the microwave extraction technique.Despite their broad range of application, a formal and comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
250
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(264 citation statements)
references
References 76 publications
9
250
5
Order By: Relevance
“…The ‘true’ δ 2 H liq and δ 18 O liq values of soil water are difficult to determine. For example, Orlowski et al . showed that for standards made of oven‐dried soil with added water, vacuum extraction does not reliably yield extracted water with the same isotope composition as the added water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ‘true’ δ 2 H liq and δ 18 O liq values of soil water are difficult to determine. For example, Orlowski et al . showed that for standards made of oven‐dried soil with added water, vacuum extraction does not reliably yield extracted water with the same isotope composition as the added water.…”
Section: Discussionmentioning
confidence: 99%
“…Distillation of soil water with heat under vacuum with cryogenic collection and subsequent liquid water analysis has been considered to be the best approach, despite evidence that it is prone to unreliable results and artefacts induced during extraction . Mechanical squeezing and centrifugation have also been used as alternative methods for physical extraction of soil water …”
mentioning
confidence: 99%
“…The isotope difference is thus significant for δ 18 O, less significant for 17 O-excess, according to the analytical error. Although evaporative kinetic fractionation of the top soil water suctioned by the porous cup under vacuum cannot be ruled out, isotopic exchanges between the soil water and oxygenbearing phases of the rhizosphere may also have impacted the soil water isotopic composition (Bowling et al, 2017;Chen et al, 2016;Oerter et al, 2014;Orlowski et al, 2016). Hereinafter, we consider the isotope signatures of the water absorbed by the roots of F. arundinacea to be equivalent to the irrigation water that fed the saturation level at the base of the tank.…”
Section: Irrigation and Soil Watersmentioning
confidence: 99%
“…Stable isotopes provide evidence for assessing plant water sources according to their variations caused by equilibrium and kinetic isotopic fractionation mechanisms (Orlowski et al, 2016a;Haverd et al, 2011;Zhao et al, 2013;Bhatia et al, 2011). Several studies (Liu et al, 2013;Mathieu and Bariac, 1996;Allison and Barnes, 1985) have shown that transpiration do not cause isotopic fractionation of soil water.…”
Section: Introductionmentioning
confidence: 99%